Stressors and coping strategies among frontline nurses during COVID-19 pandemic - I K Rohisha; Donel Jissa; M Jibin; Mathew Binu (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: Frontline nurses are more likely to be in close contact with COVID-19 patients and COVID ward duties make nurses to undergo serious emotional disturbances. The physical, psychological, and social well-being of the nurses can be affected in this time and proper training programs and counseling sessions should be undertaken. This study attempts to understand the stressors and coping strategies of nurses from a tertiary hospital. MATERIALS AND METHODS: Descriptive survey design was adopted and data were collected in 2021 from 92 frontline nurses from a selected tertiary hospital in Raipur. The data collection tools used were sociodemographic proforma, structured questionnaire on stress factors, and structured checklist on coping strategies. RESULTS: The analysis was done using frequency and percentage distribution. Among the nurses, 51% reported stressors related work- and work-related environment, 50% reported stressors related to self-safety, and 52% on stressors related to family concerns. The coping strategies adopted by the nurses included realization of the fact that service to patients comes as first (75%), and availability of personal protective equipment kits, confidence in following strict protective measures (69%), talking to family members over phone daily (71%), and support from family and friends (70%). Learning about COVID-19 (65%), and team work (61%) also created confidence to work as frontline nurses during this pandemic. CONCLUSION: The present survey reports that nurses face various stressors and tries to impart different coping strategies to overcome the stress. Understanding their stressors and coping strategies will help the administration to implement measures to create a working situation which will strengthen the health man power resources.